Evaluation of health-related quality of life and symptoms in patients with advanced non-squamous non-small cell lung cancer treated with nivolumab or docetaxel in CheckMate 057. (October 2018) - Reck, Martin; Brahmer, Julie; Bennett, Bryan; Taylor, Fiona; Penrod, John R.; DeRosa, Michael; Dastani, Homa; Spigel, David R.; Gralla, Richard J.
Abstract: Background: Nivolumab, a programmed death-1 inhibitor, prolonged overall survival and had a favourable safety profile versus docetaxel in previously treated patients with advanced non-squamous non-small cell lung cancer (NSCLC) in the phase III CheckMate 057 trial. Aim: To evaluate health-related quality of life (HRQoL) using patient-reported outcomes. Methods: Disease-related symptoms and general health status were assessed using two validated patient-reported instruments, the Lung Cancer Symptom Scale (LCSS) and the European Quality of Life Five Dimensions (EQ-5D), respectively. The proportion of patients with disease-related symptom improvement at 12 weeks on the LCSS average symptom burden index (ASBI) was a secondary end-point. LCSS 3-item global index (3-IGI), EQ-5D utility index and EQ-5D visual analogue scale (VAS) scores were also determined. Mixed-effects model repeated measures (MMRM) and time to first deterioration analyses assessed longitudinal changes. Results: Mean baseline LCSS ASBI scores were similar in both arms. By week 12, rates of disease-related improvement (95% confidence interval) were similar between nivolumab (17.8% [13.6–22.7]) and docetaxel (19.7% [15.2–24.7]); however, numerical differences in LCSS ASBI mean change from baseline favoured nivolumab. Subsequently, LCSS ASBI scores improved with nivolumab and worsened with docetaxel, with statistically significant between-arm differences at weeks 12, 24, 30 and 42. HRQoL improvements with nivolumab versus docetaxel were also supported by the LCSS 3-IGI, EQ-5D VAS and MMRM analysis. Time to first HRQoL deterioration was longer with nivolumab than with docetaxel. Conclusion: Nivolumab improved disease-related symptoms and overall health status versus docetaxel for second-line treatment of advanced non-squamous NSCLC. Clinical trial registration: NCT01673867 . Highlights: Nivolumab provided improvements in health-related quality of life in CheckMate 057. Docetaxel was associated with stable or worsening of quality of life. Disease-related deterioration was delayed with nivolumab versus docetaxel.